CHIAPAS PSITTACID CONSERVATION PROGRAM: CONSENSUAL ACTIONS IN FAVOR OF THEIR SPECIES - Altamirano-González Ortega, Marco Antonio (Kuxulkab’, 2023)
Conservation programs contribute to the fulfillment of actions for sustainable development, through the generation of synergies of commitments agreed upon by consensus. The elaboration process that for the generation of the Chiapas Psittacine Conservation Program (parrots, parakeets, parakeets and macaws) is presented. Details of its preparation are presented from the creation of an institutional group, the holding of a specialist workshop, the drafting and consensus of the document, to the implementation of activities. The importance of consensus for the elaboration of this type of documents is pointed out, where the mechanism presented can be replicated in subsequent issues of Conservation Programs. The participatory creation process and the implementation proposals agreed upon in this management instrument ensure the application of effective activities to benefit the conservation of priority species for conservation and their habitats.